Information technology project risk management in Peru - Del Carpio Gallegos, Javier (2008)
This article shows how some principles, uses, and practices of risk management are applied in information technology projects in Peru; in the last four years, in representative sectors like manufacturing, banking, information and communications, academics institutions, construction, government, consulting, services, and others.